Optic nerve, superior colliculus, visual thalamus, and primary visual cortex of the northern elephant seal (Mirounga angustirostris) and California sea lion (Zalophus californianus). Issue 9 (17th March 2017) - Turner, Emily C.; Sawyer, Eva K.; Kaas, Jon H.
Abstract: The northern elephant seal ( Mirounga angustirostris ) and California sea lion ( Zalophus californianus ) are members of a diverse clade of carnivorous mammals known as pinnipeds. Pinnipeds are notable for their large, ape‐sized brains, yet little is known about their central nervous system. Both the northern elephant seal and California sea lion spend most of their lives at sea, but each also spends time on land to breed and give birth. These unique coastal niches may be reflected in specific evolutionary adaptations to their sensory systems. Here, we report on components of the visual pathway in these two species. We found evidence for two classes of myelinated fibers within the pinniped optic nerve, those with thick myelin sheaths (elephant seal: 9%, sea lion: 7%) and thin myelin sheaths (elephant seal: 91%, sea lion: 93%). In order to investigate the architecture of the lateral geniculate nucleus, superior colliculus, and primary visual cortex, we processed brain sections from seal and sea lion pups for Nissl substance, cytochrome oxidase, and vesicular glutamate transporters. As in other carnivores, the dorsal lateral geniculate nucleus consisted of three main layers, A, A1, and C, while each superior colliculus similarly consisted of seven distinct layers. The sea lion visual cortex is located at the posterior side of cortex between the upper and lower banks of the postlateral sulcus, while the elephant seal visual cortex extends far more anteriorly along the dorsal surface and medial wall. These results are relevant to comparative studies related to the evolution of large brains. Abstract : The authors show that the visual neuroanatomical structures of the northern elephant seal (shown here) and California sea lion are organized as in other carnivores. Most notably, the presumptive primary visual cortex in each species is large and distinct, which suggests the importance of this sensory modality in pinnipeds.